The Elliot Lake Uranium Miners’ Battle to Gain Occupational Health and Safety Improvements, 1950–1980 - MacDowell, Laurel (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2012)
Uranium miners in Elliot Lake went on a wildcat strike in 1974 to protest their occupational health concerns on the job after a spike in cancer cases. They learned that the provincial government had known of the poor working conditions causing their illnesses, but had not informed them of the dangers or acted to improve their situation. As a result of union and political pressure, the Ontario government created the Ham Commission to investigate and make recommendations. Its hearings revealed the industry’s scandalous conditions, and its report eventually resulted in the Ontario Health and Safety (ohs) Act in Ontario. It did not cover the miners until 1984, so they worked through their internal health and safety committees to gain improvements in the work environment. Others have discussed this situation in relation to the emergence of the ohs and environmental movements. This paper discusses the events in terms of the mine owners’ attitudes towards their employees, the industry’s relationship to governments, and the impact of the uranium mining industry (part of the nuclear industry) on the local community and environment.